Exploiting the carboxylate chemical shift to resolve degenerate resonances in spectra of 13C-labelled glycosaminoglycans - Colebrooke, Simon A (Magnetic resonance in chemistry : MRC, 2005)
Copyright (c) 2005 John Wiley & Sons, Ltd.